The repellent and antifeedant activity of Myrica Gale oil against Aedes aegypti mosquitoes and its enhancement by the addition of salicyluric acid. - Blackwell, A; Stuart, AE; Estambale, Benson B. (Physicians Edinb., 2003)
A clinical trial was carried out with Aedes aegypti (Ae aegypti) mosquitoes to investigate the repellant and antifeedant activity of oil of Myrica gale (M. gale) and its enhancement by salicyluric acid. Myrica gale was effective as both a repellant and an antifeedant and was in a similar class of efficiency with N, N-diethyl-m-toluamide (DEET), the classical synthetic insect repellant. Salicyluric acid gave partial protection with a 10% solution and complete protection with 20% solution. Its effect appeared to be mediated by contact ’taste’ receptors, since it acted primarily as an antifeedant rather than repelling mosquitoes at a distance. The incorporation of oil of M. gale with salicyluric acid in a single formulation (where there’s a possibility of synergism) resulted in a superior product in terms of both repellency and antifeedancy. The potential contribution of these compounds to a generation of new, safer and more effective repellents is discussed.